Correlation between Dental Maturity by Demirjian Method and Skeletal Maturity by Cervical Vertebral Maturity Method using Panoramic Radiograph and Lateral Cephalogram - Madhusudhanan Mallika Mini; Valsa Thomas; Tinky Bose (Wolters Kluwer Medknow Publications, 2017)
Introduction: Radiographs are effective tools in assessing the stages of bone maturation in dentistry. The cervical vertebral maturation method is a proven effective tool in assessing the adolescent growth spurt than hand-wrist radiographs in an individual. Assessment of dental calcification stages are a reliable method for determining dental maturity. Panoramic imaging can be used as the primary imaging modality for assessing maturity if a correlation can be found out between tooth calcification stages and cervical vertebral maturation stages. This study was conducted to determine the correlation between dental maturity stage and cervical vertebral maturity stage and to estimate predictor variables for cervical vertebral maturation stages (CVMS) stratified by gender in a tertiary hospital setting. Materials and Methods: A descriptive study was conducted among patients accessing orthodontic care in radiology outpatient clinic, Oral Medicine and Radiology department, Government Dental College Thiruvananthapuram for a period of 15 months. Participants were selected between the ages of 8 and 16 years. Panoramic radiographs and lateral cephalograms were used to determine dental maturity stages using Demirjian method and CVMS using Bacetti and Franchi method, respectively. Results: One hundred patients (males = 46, females = 54) were included in the study; the spearman rank order correlation revealed significant relationship. The correlation ranged from 0.61 to 0.74 for females and 0.48 to 0.51 for males. Second premolar showed highest correlation and canine the lowest for both females and males. Stage G of mandibular second premolar signifies the pubertal growth period in this study population. By ordinal regression model, G stage of second premolar was found to be a significant predictor in males and stage H followed by G and F in females for the age group of 12-14 years. Conclusion: Dental maturation stages were significantly correlated with CVMS. The development stages of mandibular second premolar had the strongest correlation with cervical vertebral maturity in both males and females. G stage of mandibular second premolar can be clinically used as a maturity indicator in the pubertal growth period. Moreover, G stage of second premolar can be used as a significant predictor for the age group of 12-14 years in both males and females.